Acupuncture for gastrointestinal urticaria: A protocol for systematic review and network meta-analysis - Li, Yiwei; Zhang, Leixiao; Wang, Qiong; Deng, Yanli (Frontiers in Medicine, 2022)
Introduction: The purpose of this review is to evaluate the effectiveness and safety of acupuncture in the treatment of patients with gastrointestinal urticaria (GU) and to provide a clinician’s guide to GU treatment options. Methods and Analysis: We plan to search multiple databases (i.e., PubMed, EMBASE, Springer, Web of Science, Cochrane Library, China National Knowledge Infrastructure, Chinese Biomedical Literature Database and Wanfang Database) for studies published before September 1, 2022. We will electronically search for all relevant studies concerning clinical acupuncture treatments of GU, including unpublished conference articles and other grey literature. The language limit of this systematic review is Chinese and English. Any reports of clinical randomised controlled trials of acupuncture for the treatment of GU will be included in the study. Two researchers will perform independent data extraction to increase the quality of the data extraction. The primary outcome was the Urticaria Activity Score 7 (UAS7). Abdominal visual analogue scale (VAS) for abdominal pain, dermatological life quality index (DLQI), the total effective rate, recurrence rate, and occurrence of adverse events were secondary outcomes. We will use RevMan V.5.3 statistical software for pairwise meta-analysis and ADDIS V.1.16.8 software for Bayesian network meta-analysis. If feasible, meta-regression and subgroup analyses will also be performed to address the potential causes of inconsistency and heterogeneity. We will conduct a GRADE assessment of the quality of evidence for the interventions included in this review. Discussion: This study may validate acupuncture as an alternative therapy for the effective treatment of GU.